MAXIMS VIOLATION ON “NIGHT AT THE MUSEUM” MOVIE - Andy Andy; Ambalegin Ambalegin (Universitas Putera Batam, 2019)
This research was created based on concerning the importance of efficient language use. The language use can be called efficient if the message is clear, unambiguous and can be understood by both speaker and hearer. Cooperative principles proposed by Grice (1975) explained the way people use the language well and efficiently. There are at least four maxims that should be followed in order to have achieve connection during conversation which are 1) maxim of manner, 2) maxim of quantity, 3) maxim of quality, and 4) maxim of manner. In fact, there are several maxim violations happened in human life especially figured in the movie. The maxim violations may cause misunderstanding while the conversation is going on. This paper aims to analyze the maxim violations that exist in the movie titled Night at the Museum 1. It uses descriptive qualitative method with pragmatics identity analysis. The findings show that maxim of manner and quantity are the dominant maxims which are violated.